The Intersection of Aging, Longevity Pathways, and Learning and Memory in C. elegans - Stein, Geneva M.; Murphy, Coleen T. (Frontiers in Genetics, 2012)
Our understanding of the molecular and genetic regulation of aging and longevity has been greatly augmented through studies using the small model system, C. elegans. It is important to test whether mutations that result in a longer life span also extend the health span of the organism, rather than simply prolonging an aged state. C. elegans can learn and remember both associated and non-associated stimuli, and many of these learning and memory paradigms are subject to regulation by longevity pathways. One of the more distressing results of aging is cognitive decline, and while no gross physical defects in C. elegans sensory neurons have been identified, the organism does lose the ability to perform both simple and complex learned behaviors with age. Here we review what is known about the effects of longevity pathways and the decline of these complex learned behaviors with age, and we highlight outstanding questions in the field.